CONCEPTUAL CORRESPONDENCE THROUGH MENTAL SPACE IN CREATING WORDS AT THE NOVEL HARRY POTTER AND THE SORCERERS STONE - Ariyani Pedo, Venansia Ajeng Surya (Universitas Esa Unggul, 2019)
AbstractThe aim of the research was to find out the process of conceptual correspondence of the mental space J. K. Rowling has when producing new words in